Penerapan Teknik Reality Terapy untuk Mengurangi Perilaku Membolos pada Siswa di Sekolah Menengah Atas - Devi Siling; Nobertin Derita Marimbun; Sarce La bi (Nubuat : Jurnal Pendidikan Agama Kristen dan Katolik, 2026)
Truancy among high school students continues to be a serious concern that has negative effects on both academic outcomes and social development. This study seeks to analyze the application of reality therapy as an intervention to minimize truancy behavior. The research utilizes a literature review approach by evaluating six relevant scholarly articles published over the past decade. The findings suggest that truancy is caused by a combination of internal factors, such as lack of learning motivation and feelings of boredom, and external factors, including family environment and peer influence. Conventional approaches that rely heavily on punishment and external control are considered less effective in creating lasting behavioral improvements. On the other hand, reality therapy emphasizes personal responsibility, present actions, and self-assessment, allowing students to better understand their behavior and make more positive decisions. The results demonstrate that this approach enhances students’ self-awareness, responsibility, and decision-making abilities. Therefore, reality therapy can be regarded as an effective alternative counseling method to address truancy behavior in schools and to support long-term behavioral change.